Mavka : the forest song [videorecording (DVD)] - Voytseshek, Yaroslav (Shout! Kids ; Universal, 2023)
Mavka the soul of the forest has been chosen by the supreme spirits to become the forest's new guardian. But when she meets a talented human musician named Lucas a man on the hunt for a mysterious tree with the power to give life, she is faced with an impossible choice between her newfound love and her duty to the spirits. Can humans and the forest live in harmony, or will greed and vice destroy them both?